BIOLOGY OF RUBIA TINCTORUM (RUBIA TINCTORUM L) DISTRIBUTED IN SURKHANDARYA REGION AND ITS USE IN MEDICINE - Begmatov Abdusamat; Mirzaeva Khadicha Yuldashevna (American Journals, 2022)
In this article, the biology of the plant Rubia tinctorum L, the mineral substances contained in the root, and the information about its use in medicine are highlighted.
Keywords: Rubia tinctorum L, anthracene, alizarin, ruberythric acid, galiosin, purpurin,xanthopurpurin, pseudopurpurin, rubiadin- glucoside, ibericin, urinary tract stone, kidney stone, gout.